Tooth Autotransplantation Part 1: uses, indications and factors affecting success. (2nd April 2019) - Monteiro, Joana; Barber, Sophy; Jawad, Zynab; Duggal, Monty; Houghton, Nadine
Abstract : Management of severe traumatic injuries and complex dental anomalies in children requires a holistic approach with planning for both short- and long-term eventualities. The goal is to provide biological treatment that maximizes the long-term dental health, appearance and function. Tooth autotransplantation is one potential solution for tooth replacement that is able to fulfil these aims. This series of four articles provides an overview of autotransplantation, including a description of the biological basis for the technique and factors affecting success. It will also provide an outline of the indications and the procedures involved for performing autotransplantation, including the interdisciplinary approach to treatment planning and management. This first article discusses the history of tooth transplantation, indications and the factors that can influence outcome. CPD/Clinical Relevance: Orthodontists should be aware that tooth autotransplantation is a highly versatile technique with good success rates if used in favourable cases. This method should be considered part of the armamentarium for tooth replacement in a growing child.